Counseling on Sexual Education and the Dangers of Narkolema to Residents of the Budi Perkasa Center - Diana Arini; Erma Soesilowati; Sherly Marcela; Angelina Septiani (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2023)
The participants of Budi Perkasa Rehabilitation and Social Protection are people who have social and fostered problems. The aim of the activity is to provide curative counseling about sexual education and the effects of Narkolema. The activity was carried out on September 16, 2022 in the Budi Sentra hall by giving lectures, watching videos and discussions. The number of participants who took part in the activity was 34 participants (22 men and 22 women). Data collection was carried out by giving a pre test and post test containing activity material. Based on the results of the Mann Whitney analysis, we find that the pre-test and post-test score is 0.004 (p <0.05), meaning that there is a change in the participants' knowledge before and after the implementation of the extension activities. Additional analysis see from the activeness of the participants in the discussion and their questions, the enthusiasm of the participants ask more about biological problems in sexual education and health problems. Suggestions for future researchers to provide more portions of sexual education counseling in biology and health for marginalized people or those who are sexually active.